Clinical presentation and outcome of Thai patients with chronic lymphocytic leukemia: Retrospective analysis of 184 cases - Tharinee Sriphatphiriyakun (2018)
Chronic lymphocytic leukemia (CLL), which is the most common leukemia in adult population in the Western world, is surprisingly rare in Thailand. The objective of our study was to retrospectively analyze the clinical presentations and outcome of a large cohort of Thai CLL patients diagnosed at a single institution in Bangkok, Thailand, from 1963-1998. One hundred and eighty-four patients were included in the study. The most frequent age group was 60-80 years old with the male to female ratio of 2:1. Only 12% of patients were younger than the age of 50. Most patients were from the central agricultural region of Thailand. Clinical findings at presentation included splenomegaly (64%), lymphadenopathy (60%), anemia (54%), hepatomegaly (49%), fatigue (39%), weight loss (33%), fever (21%), thrombocytopenia (18%), and anorexia (8%). Only 8% of Thai CLL patients were asymptomatic at presentation. The majority of patients were categorized as stages III and IV with the median survival of 20 months and 8 months, respectively. Infection was the most common cause of death, particularly in the elderly patients who had comorbid illnesses. Twenty-two percent of the patients had associated autoimmune disorders. The unfavorable prognostic factors observed were older age (> 70 years), weight loss and hepatosplenomegaly. We concluded that the age and gender of Thai CLL patients were similar to those of the Western countries but our patients came to medical attention at a later and more advanced stage. Prospective studies at a multi-center level in Thailand should be pursued to investigate further the genetic and epidemiologic nature of Thai CLL patients.